2014
DOI: 10.1185/03007995.2014.909390
|View full text |Cite|
|
Sign up to set email alerts
|

Dose-finding study of luseogliflozin in Japanese patients with type 2 diabetes mellitus: a 12-week, randomized, double-blind, placebo-controlled, phase II study

Abstract: Objectives: Luseogliflozin is a selective sodium glucose cotransporter 2 inhibitor under development for the treatment of type 2 diabetes mellitus (T2DM). This phase II study was conducted to confirm the efficacy and safety of luseogliflozin monotherapy at doses of up to 10 mg in Japanese patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 29 publications
3
52
1
Order By: Relevance
“…*P< 0.001 (compared to baseline using the one-sample t-test). CI, confidence interval; FPG, fasting plasma glucose; HbA1c, hemoglobin A1c; SD, standard deviation ies [6,7,11]. It was also comparable to that observed in a 52-week study of sitagliptin (1.7%), a DPP-4 inhibitor known for its low incidence of hypoglycemia when administered as monotherapy [12].…”
Section: (Compared With Baseline By One-sample T-test)supporting
confidence: 73%
See 2 more Smart Citations
“…*P< 0.001 (compared to baseline using the one-sample t-test). CI, confidence interval; FPG, fasting plasma glucose; HbA1c, hemoglobin A1c; SD, standard deviation ies [6,7,11]. It was also comparable to that observed in a 52-week study of sitagliptin (1.7%), a DPP-4 inhibitor known for its low incidence of hypoglycemia when administered as monotherapy [12].…”
Section: (Compared With Baseline By One-sample T-test)supporting
confidence: 73%
“…In addition, no patients experienced ketoacidosis. Further, previous studies of luseogliflozin showed a post-meal rapid decrease in fasting ketone bodies [6,7]. Given that luseogliflozin will be administered to patients comprising various metabolic types in clinical practice, further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are registered at the Japan Pharmaceutical Information Center (identifier: JapicCTI‐090908, JapicCTI‐101191 and JapicCTI‐111661)2, 3, 4. The major inclusion criteria were as follows: Japanese patients with type 2 diabetes mellitus receiving diet and exercise therapy alone, age ≥20 years and with glycated hemoglobin levels ≥6.9% to ≤10.5%.…”
mentioning
confidence: 99%
“…Studies in Japanese patients with T2DM have confirmed that treatment with luseogliflozin increases urinary glucose excretion (UGE) and reduces plasma glucose levels. [7][8][9][10][11][12] In a clinical pharmacology study conducted in Japanese patients with T2DM, reported by Sasaki et al, intensive sampling of UGE (nine sampling intervals a day) was performed and UGE change from pre-dose was analyzed; a significant increase in UGE was observed with once-daily luseogliflozin administration. The UGE was dose-dependent and the relationship of change in daily UGE and area under the curve (AUC) 0-24h of plasma luseogliflozin could be expressed by means of the E max model.…”
Section: -4)mentioning
confidence: 99%